2006
DOI: 10.1016/j.cub.2006.09.015
|View full text |Cite
|
Sign up to set email alerts
|

Selenium-Tolerant Diamondback Moth Disarms Hyperaccumulator Plant Defense

Abstract: Although Se hyperaccumulation protects plants from herbivory by some invertebrates, it can give rise to the evolution of unique Se-tolerant herbivores and thus provide a portal for Se into the local ecosystem. In a broader context, this study provides insight into the possible ecological implications of using Se-enriched crops as a source of anti-carcinogenic selenocompounds and for the remediation of Se-polluted environments.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

6
174
0
2

Year Published

2008
2008
2023
2023

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 122 publications
(182 citation statements)
references
References 48 publications
(63 reference statements)
6
174
0
2
Order By: Relevance
“…Third, it can produce microscopic maps of chemical species.To our knowledge, XAS imaging has not been carried out on insects, and relatively little on organisms in general, although µ-XRF imaging of selenium localisation was carried out on high-concentration selenium-fed diamondback moth larvae (Plutella xylostella) inhabiting selenium hyperaccumulating plants. [25] Fig. 2 shows images of two different bertha armyworm larvae.…”
Section: Arsenic Speciation Using X-ray Absorption Spectroscopymentioning
confidence: 99%
“…Third, it can produce microscopic maps of chemical species.To our knowledge, XAS imaging has not been carried out on insects, and relatively little on organisms in general, although µ-XRF imaging of selenium localisation was carried out on high-concentration selenium-fed diamondback moth larvae (Plutella xylostella) inhabiting selenium hyperaccumulating plants. [25] Fig. 2 shows images of two different bertha armyworm larvae.…”
Section: Arsenic Speciation Using X-ray Absorption Spectroscopymentioning
confidence: 99%
“…These larvae were documented through laboratory tests to tolerate the hyperaccumulated Se (2,000 mg kg 21 dry weight) in S. pinnata leaves and not to be deterred by high-Se plants. In contrast, a diamondback moth population collected and reared from a nonseleniferous area in the eastern United States quickly died after feeding on high-Se leaves and was deterred by high-Se S. pinnata plants (Freeman et al, 2006a). A potential mechanism for the difference in Se tolerance between the two moth populations was revealed by mXANES and LC-MS analyses, which demonstrated that the Se-tolerant moth accumulated MeSeCys, similar to its host plant S. pinnata, whereas the Se-sensitive population accumulated SeCys and had obvious disintegration of internal organs (Freeman et al, 2006a).…”
mentioning
confidence: 98%
“…Hyperaccumulator plants may host Se-tolerant herbivores, as shown in a previous study that reported a Se-tolerant moth species associated with S. pinnata (Freeman et al, 2006a). Larvae from a population of Setolerant Plutellidae closely resembling the diamondback moth (Plutella xylostella), a damaging agricultural pest, were collected from S. pinnata in a seleniferous area (Fort Collins, CO).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The hyperaccumulators Astragalus bisulcatus and Stanleya pinnata were found to predominantly accumulate Se in peripheral tissues of young leaves and reproductive organs: in structures important to protect, prone to herbivore and pathogen attacks, and/or typically associated with playing a defensive role (Pickering et al, 2003a;Freeman et al, 2006b;Galeas et al, 2007). Indeed, laboratory and field studies have shown that Se can protect plants from various herbivores and fungal pathogens (Vickerman and Trumble, 1999;Bañ uelos et al, 2002;Hanson et al, 2003Hanson et al, , 2004Freeman et al, 2006aFreeman et al, , 2007Freeman et al, , 2009Galeas et al, 2008;Quinn et al, 2008).…”
mentioning
confidence: 99%